DO THE OFFSPRING OF CENTENARIANS HAVE GOOD HEALTH HABITS?. (11th November 2018) - Drury, J; Sidlowski, S; Leonard, B; Hsu, M; Mostowy, M; Andersen, S; Perls, T
Abstract: Introduction: Per previously published work, centenarian offspring have delayed disease onset and lower overall morbidity. Families not only have genetic variations in common, they also likely have important health-related behaviors in common as well. We sought to evaluate differences between the health behaviors of centenarian offspring and a referent cohort without familial longevity. Methods: Our sample consisted of 578 centenarian offspring and 337 controls from the New England Centenarian Study (mean age 70.7 +/- 7.3 years, 56% female). Controls were birth cohort matched individuals without parental exceptional longevity. We examined alcohol consumption, past/current smoking, body mass index (BMI), social networks, and dental health habits. We used chi-square tests to compare the proportions of centenarian offspring and referents for each health habit category. Results: Centenarian offspring were less likely to have ever smoked (p=.006), were more likely to have a BMI within the healthy range (p=.02), were more likely to visit a dentist at least once per year (p<.001), and were more likely to brush their teeth at least once per day (p=.01). We did not find significant differences in alcohol consumption or social networks. Conclusions: Centenarian offspring were more likely to have some healthy behaviors than the controls. We do not know to what degree these behaviors were learned from their parent who went on to be a centenarian; nor do we know to what degree such behaviors have some genetic component. However, clearly healthy behaviors explain an important part of the offsprings' delay of diseases and survival advantage.